Creative Economy Development in Enhancing Sustainable Tourism Potential in Kutai National Park, East Kalimantan - I Gusti Made Juniarta; Cing Cing Wahyuni; Pungky Dios Purnomo; Apri Kuntariningsih (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2026)
This research investigates the integration of the creative economy as a catalyst for sustainable tourism development within Kutai National Park (KNP), East Kalimantan. Despite its ecological significance as a lowland rainforest and Orangutan habitat, KNP faces stagnation due to a reliance on extractive resources and a lack of diversified tourism products. Employing a qualitative descriptive methodology and SWOT analysis, this study maps the creative potential of the region and evaluates its impact across four sustainability pillars: economic, social, environmental, and institutional. Data were gathered through field observations and in-depth interviews with park authorities, local government officials, and creative entrepreneurs in the buffer zones of Sangatta and Bontang. The findings reveal significant potential in non-timber forest-based culinary arts, modernized ethnic crafts, and digital wildlife storytelling. A critical institutional barrier identified is the